Detection of Helicobacter Pylori IgG and IgA , Serum Biomarkers CA19-9 and CEA in Patients with Gastrointestinal Diseases - R. Kadhim, Shurooq; H. Alaiwi, Ishraq; R., Rasha (Iraqi Journal of Pharmaceutical Sciences, 2017)
Gastrointestinal diseases and especially chronic gastritis are mainly induced by Helicobacter pylori infection, and provides the basis for gastric carcinogenesis and colorectal cancer. The study involved the detection of serum anti-H. pylori IgG and IgA antibody of and some serum biomarkers ;CEA and CA19-9 in patients with gastrointestinal diseases. Fifty eight serum samples were collected from 25 males and 33 females .Peripheral venous blood was collected from each patient and sera obtained by centrifugation. Serum anti-H. pylori IgG and IgA ,serum CEA and CA19-9 were evaluated by enzyme-linked immunoadsorbent assays (ELISA).Forty eight serum samples were positive for IgG (82.7% ) divided into 27 positive samples for females and 21 positive samples for males while ten samples were positive for IgA ( 17.2%) divided into eight positive samples for females and two positive samples for males .Only three samples were positive for anti IgG and serum biomarker CA19-9 .In this study most of positive results of H.Pylori IgA and IgG are between the age 30-50 years and low within 1-10 years ,we conclude because most of them are working and eat fast food from different sources. This study concluded that detection of serum IgG and IgA is effective in monitoring the H. pylori infection in gastrointestinal disorders and chronic infections . Keywords: Gastrointestinal diseases, Gastritis , H.Pylori, IgG ,IgA ,CEA,CA19-9.